2011
DOI: 10.1128/iai.00025-11
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptor 4 and Downstream Effectors in Selected Cecal Cell Subpopulations of Chicks Resistant or Susceptible to Salmonella Carrier State

Abstract: Toll-like receptor 4 (TLR4), which recognizes lipopolysaccharide from Gram-negative bacteria, plays a major role in resistance of mice and humans to Salmonella infection. In chickens, Salmonella may establish a carrier state whereby bacteria are able to persist in the host organism without triggering clinical signs. Based on cellular morphological parameters, we developed a method, without using antibodies, to separate three cecal cell subpopulations: lymphocytes, enterocytes, and a population encompassing mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Chen et al (2007) showed that increased TLR2b levels are associated with enhanced gastrointestinal epithelial barrier function against pathogens. Various studies have implicated TLR4 in recognition of glucuronoxylomannan (Shoham et al, 2001) and Saccharomyces cerevisiae and Candida albicans derivates (Tada et al, 2002), and resistance to carrier states of Salmonella in chicks is associated with a higher level of expression of TLR4 (Sadeyen et al, 2006;Chaussé et al, 2011). In the present study, an upregulated TLR21 expression was observed in chickens on BMDand YDM-supplemented diets in the cecal tonsil and bursa of Fabricius, whereas expression in the spleen was downregulated in the YDM treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Chen et al (2007) showed that increased TLR2b levels are associated with enhanced gastrointestinal epithelial barrier function against pathogens. Various studies have implicated TLR4 in recognition of glucuronoxylomannan (Shoham et al, 2001) and Saccharomyces cerevisiae and Candida albicans derivates (Tada et al, 2002), and resistance to carrier states of Salmonella in chicks is associated with a higher level of expression of TLR4 (Sadeyen et al, 2006;Chaussé et al, 2011). In the present study, an upregulated TLR21 expression was observed in chickens on BMDand YDM-supplemented diets in the cecal tonsil and bursa of Fabricius, whereas expression in the spleen was downregulated in the YDM treatment.…”
Section: Discussionsupporting
confidence: 50%
“…Under TLR activation, heterophils can produce inflammatory mediators such as cytokines to help induce further immune responses (Farnell et al, 2003;Kogut et al, 2005). In addition, resistance to pathogens, such as Salmonella spp., has closely been associated with an upregulation of TLR, mainly TLR4, and different chemokines and cytokines (Sadeyen et al, 2006;Chaussé et al, 2011). Aberrant expression of TLR2, TLR4, and TLR21 has been associated with susceptibility to Salmonella enterica serovar Enteritidis infection in chickens (Gou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another resistance‐related factor called Toll‐like receptor 4 belongs to a family of innate immune system receptors involved in the recognition of lipopolysaccharides (LPS) from Gram‐negative bacteria (Calenge and others ; Chaussé and others ).…”
Section: Preharvest Methods For Reducing the Risk Of Salmonella Contamentioning
confidence: 99%
“…These carriers are characterized by a symptom-free condition and can act as reservoirs and hence contribute to the propagation of the disease, which is particularly important in the case of food workers. Unfortunately, there is a scarcity of results concerning the immune response and the efficacy of antimicrobial treatment in these silent infections that could be used to develop suitable prophylactic and therapeutic modalities (34)(35)(36).…”
Section: Clinical Relevancementioning
confidence: 99%